Economics, organization and management - Milgrom, Paul (Prentice-Hall, 1992)
The book is organized into seven parts. Part 1 deals with the fundamental problems of economic organization: illustrates these problems with a set of case studies; develops the economic perspective in moral detail; illustrates how these ideas are manifested in a wide variety of real institution, both public and private. Part 2 is about coordination, both by the invisible hand of prices in markets and by the quite visible hands of managers: explores the failures of the price system, scopes that are fundamental for understanding the role of management in organizations. Part 3 introduces the problems of contracting, information, and incentives, and gives an informal treatment of their solution: deals with contracting with bounded rationality and informational differences and incompleteness; treats the problems of selecting partners and negotiating and enforcing contracts. Part 4 provides a careful, formal treatment of some of the central methods of providing incentives efficiently: deals with risk sharing and incentive contracts; introduces a set of theoretical principles for efficient performance contracting and illustrates these principles with a series of significant applications; investigates theories in which those issues are irretrievably intertwined. Part 4 presents an economic treatment of the nature of the employment relationship, examining explicit and implicit employment contracts, compensation policies, and career paths: reviews the classical theory of labor markets and more modern theories that explain why long-term employment relations predomonate in every developed economy; reviews the facts and theories about the controversial matter of executive compensation. Part 6 treats financial decision, particularly in investments, capital structure, and corporate control. The last part of the book comprises two chapters about the design, internal structure, and dynamics of organizations, including examination of the boundaries and scope of business firms: identifies the problems that major organizational innovations aimed to solve and the principles that have governed past organization choices; looks ahead, emphasizing the dynamic processes that drive organization change and peering into future of capitalist firms, national economies, and the study of the economies and management of organizations